Diversity, Equity, and Inclusion Professional Development Events in Academic Libraries Have Minimal Impact on Knowledge, Behavior, and Organizational Change Without Meaningful Design and Participant Intentionality / Dali, K., Bell, N., & Valdes, Z. (2021). Learning and change through diversity, equity, and inclusion professional development: Academic librarians’ perspectives. Journal of Academic Librarianship, 47(6), 102448. https://doi.org/10.1016/j.acalib.2021.102448 - Opuda, Eugenia (Evidence Based Library and Information Practice, 2023)
Objective – To explore experiences of library diversity, equity, and inclusion (DEI) professional development events (PDEs) and to examine the long-term impacts on knowledge and personal practices of librarians and organizational changeDesign – Exploratory, qualitative survey, hermeneutic phenomenology, retrospective reflection on a critical incidentSetting – Academic libraries across the United States and CanadaSubjects – 141 survey responses from academic librarians in public and private institutions who attended a DEI PDEsMethods – The authors distributed a survey in late 2020 to librarians in public and private academic institutions across the US and Canada. Participants were asked to reflect retrospectively on memorable and impactful DEI PDEs they attended in the last five years and to focus on events at least a year before the survey was conducted. Participants were also asked to describe if the PDE changed their own learning and practice, as well as their organization’s policies and practices. The authors used hermeneutic phenomenology as a framework for their research and data analysis, which they describe as an approach to phenomenology that emphasizes the range and diversity of experiences. The survey questions were designed to illicit retrospective reflection and critical incident technique in order to capture the most impactful and memorable experiences with PDEs from respondents. Survey responses were coded, categorized, interpreted, and then mapped to the Transtheoretical Model (TTM) of change, a principle that breaks the phases of change into six processes: precontemplation, contemplation, preparation, action, maintenance, and termination. Additionally, the authors also ensured they represented diverse backgrounds as a method for addressing and reducing bias.Main Results – The authors uncovered a trove of varied experiences and perspectives related to personal as well as organizational knowledge and change. However, they identified five broader categories of learning from the study data: cognitive learning, behavioral learning and change, personal learning and change, social learning and change, and emotional learning and change. The majority of study participants (n=91) chose to attend DEI PDEs rather than being required by their organizations to attend. Many came into the PDE with goals to attain new knowledge (n=39) and to change their behavior (n=30). Similarly, respondents noted that the PDE impacted them most by giving them new awareness around DEI topics and systemic inequities (n=51) and inspired behavioral changes and a commitment to taking action (n=28). PDEs also impacted some participants’ self-awareness around their own biases and privileges (n=22). However, responses included skepticism around the impact of PDEs on any real and meaningful change, particularly related to organizational culture and action. Respondents emphasized concern about performative allyship and underscored the challenges and barriers to making DEI a meaningful component of many institutional practices and policies. While respondents noted increased awareness around systemic inequities, these responses stood in stark contrast to several comments expressing frustration at the lack of meaningful organizational change and demoralization felt at the fruitlessness of DEI PDEs. The authors’ initial data analysis revealed that PDEs most impacted cognitive awareness and behavioral action. However, when they mapped the data to the TTM, results emphasized the impact of PDEs on behavioral learning and action.Conclusion – Academic librarians who participate in DEI-related PDEs experience a wide array of emotional responses to the training and leave with a broad range of cognitive, behavioral, and affective impacts. While data suggests that these PDEs increased awareness and knowledge and behavioral action the most, there is little that suggests that meaningful organizational change follows afterwards. Another challenge is the gap between having awareness of DEI topics and taking steps toward meaningful self-improvement. The authors note that it takes time for knowledge to translate into action and highlight the importance of post-PDE check ins by PDE facilitators and library administration. Academic librarians should approach DEI PDEs with intentionality by challenging themselves to set goals and use their new DEI knowledge to create actionable change both personally and organizationally. On the other hand, creators of DEI PDEs should take time to understand the participants and organizational culture in order to design trainings intentionally, using the TTM as a guide to identify how the PDE maps to the stages of change leading to meaningful action and follow up. Without intentionality, follow up, and goal setting, DEI-related PDEs may be ineffective, performative, and demoralizing.